Pengaruh Penambahan Saccharomyces Cerevisiae dan Aspergillus Oryzae terhadap Karakteristik Eco-Enzyme serta Pengaplikasiannya dalam Pembuatan Sabun Padat Antiseptik - safrida Safrida; Suryani Suryani; Zuhra Amalia (Politeknik Negeri Lhokseumawe, 2023)
The production of eco-enzyme usually takes a long time for fermentation, which is three months using natural microbes found in fruit peels. This research is experimental by focusing on accelerating the production of the eco-enzyme using two types of microbes, namely saccharomyces cerevisiae and aspergillus oryzae whose mass is varied by 5 variations, and the fermentation time is set for 20 days. The results showed that the eco-enzyme made by adding microbes had the same characteristics as the natural fermentation eco-enzyme. Furthermore, the eco-enzyme obtained from the research was added as an antiseptic in making solid soap. From the test results, the best inhibitory power was obtained in the eco-enzyme with the addition of saccharomyces cerevisiae as much as 10 g and aspergillus oryzae as much as 25 g. The inhibitory power test was carried out by comparing the number of bacteria present on unwashed hands with hands that had been washed using soap. The test results showed the number of bacteria on unwashed hands was 85 CFU, which were washed using samples with aspergillus oryzae as much as 4 CFU, with saccharomyces cerevisiae as much as 2 CFU, this inhibition is better than commercial antiseptic soap with a total of 8 CFU